New rhetoric, read in concept and trends - Hassaine, Rabah Mohamed; Bensenoussi, Souad (Journal of Human Sciences, 2022)
Rhetoric is one of the most important central tools of the approach to the text, as it is the university of two basic paths, a argumentative path, a stylistic course, rhetoric often dealing with texts and literary discourses governed by awareness and intent, and this has made it re-examine rhetorical techniques that would create or increase the degree of consent of others to the thesis submitted to them with the intention of accepting them and conviction, and they are establishing a bridge between poetry and rhetoric, between imagination and deliberation under the so-called public eloquence. This study examines the ways in which the concept shifts from old rhetoric to new rhetoric, especially since the latter has made social relations a priority of their work, which has resulted in an interest in the persuasive aspect - the rhetoric of persuasion - which is based on the culture of communication and persuasion, as well as the demonstration of their function, and the trends of this new rhetoric.